Penggunaan Realia dalam mengajarkan English Guiding untuk Asidewi Desa Wisata Kampung Patin - Syaifullah, Syaifullah; Refika andriani (Indra Institute Research & Publication, 2024)
This research aims to describe the results of using Realia to increase the ability to guide in English ASIDEWI in the tourist village of Patin village, Koto Masjid village, XIII Koto Kampar sub-district, Riau. This research uses the Classroom Action Research method which has several procedures in each cycle. For one procedure cycle there are four; Planning, Action, Observation, Reflection. After running one cycle, a total of four meetings, researchers have found results from the use of realia in English guiding which has been practiced by ASIDEWI. To find out the results of applying Realia in teaching English Guiding, at the end of the meeting, the researcher gave a test, namely the guiding test in English. The test results show that there is no improvement in ASIDEWI's English Guiding ability by using realia. This occurs due to several factors that have been obtained through Qualitative Data. First, ASIDEWI members do not have sufficient knowledge of English. Generally, ASIDEWI members have a diploma at the Senior High School (SMA) level. Second, ASIDEWI members are not yet confident or shy about speaking English. Third, ASIDEWI has a very minimal vocabulary. In conclusion, ASIDEWI's ability in English Guiding whether using realia media or not using media is the same.